Forest management and terraced agriculture: case study of Hani of Ailao mountains, Yunnan - Wang Qinghua (2001)
This case study of the Hani in the Ailao mountains of Yunnan, China, highlights the importance of forests in providing local ecological services that are essential for the system of terraced agriculture. The paper investigates local people's knowledge of these ecological services, including water regulation and nutrient recycling, as well as the gender differences in the local knowledge of these services. The paper notes that the Hani have maintained the forest condition quite irrespective of its tenurial status. Contemporary forest policies and reforestation in the area are also discussed.